2007
DOI: 10.1007/s10853-007-1683-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-yield tensile set of a semi-crystalline polymer, its blend and composite

Abstract: Tensile set was studied at low strains on polypropylene, aliphatic polyketone, rubber toughened blends and CaCO 3 particle toughened composites. The rubber in the rubber toughened blends had a particle size of 0.7 lm. The CaCO 3 particles had a size of 0.7 lm and had been coated with stearic acid.Step-cyclic loading was applied in 1% strain incrementals at a strain rate of 10 -2 s -1 . The maximum strain applied was 20%. The temperature of the test bar was studied with an infra-red camera. Pre-yield deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The stress-strain curve eventually became an inverted "S" shape, which was resembling to the stress-strain curve expressed by the non-Gaussian statistical model of rubber elasticity [46,47]. This result differed markedly from those reported previously for various plastics [29,[31][32][33][34][35][36][37][39][40][41]. The present result suggested that rubber-like deformation occurred during the reloading process.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…The stress-strain curve eventually became an inverted "S" shape, which was resembling to the stress-strain curve expressed by the non-Gaussian statistical model of rubber elasticity [46,47]. This result differed markedly from those reported previously for various plastics [29,[31][32][33][34][35][36][37][39][40][41]. The present result suggested that rubber-like deformation occurred during the reloading process.…”
Section: Resultscontrasting
confidence: 59%
“…Therefore, various approaches have been developed to clarify the plastic deformation behavior of polymers. One of the phenomenological methods to characterize plastic deformation is loading, unloading, and reloading cyclic tests [29][30][31][32][33][34][35][36][37][38][39][40][41], which are also used to investigate the Bauschinger effect [30]. In glassy plastics, the residual strain after an unloading process, i.e., plastic strain, is proportional to the applied strain beyond the yield point [29,34,37].…”
Section: Introductionmentioning
confidence: 99%
“…For calculating crystallinity in copolymer, the peak height of 1630 ( h (1630 cm −1 ) ) and the peak height at 1660–1670 ( h (1670 cm −1 ) ) are taken to represent crystalline and their amorphous segments, respectively. Similar calculations are performed on several amides containing TPEs …”
Section: Resultsmentioning
confidence: 99%